(untitled) (Indian Journal of Animal Production and Management, 2015)
Relationship of 6 linear body measurements (body length, height at wither, rump height, heart girth, sacral pelvic width and rump length) on body weight of 68 adult (2-5 years) female Assam Hill goat was investigated using path analysis. The phenotypic correlations among body weight and linear body measurements were found to be positive. The correlation of body weight was found to be highest with body length (0.86) followed by heart girth (0.79). The strongest direct effect on body weight was found for heart girth (0.593) followed by body length (0.536). Indirect effects of other linear measurements were either through heart girth or body length. The optimum multiple regression equation for weight estimation included body length, heart girth, sacral pelvic width and rump length with coefficient of determination of 82.4 per cent. The results obtained in the present investigation could be helpful in weight estimation, selection and breeding program of Assam Hill goat.